OPTIMIZATION OF COLLIMATOR APERTURE GEOMETRY FOR BNCT KARTINI RESEARCH REACTOR USING MCNPX - Ramadhan Valiant Gill S.B.; Yohannes Sardjono (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2019)
Boron Neutron Capture Therapy (BNCT) is one of the promising cancer therapy modalities due to its selectivity which only kills the cancer cells and does not damage healthy cells around cancer. In principle, BNCT utilizes the high ionization properties of alpha (4He) and lithium (7Li) particles derived from the reaction between epithermal and boron-10 neutrons (10B + n → 7Li + 4He) in cells, where trace distance of alpha and lithium particles is equivalent with cell diameter. The neutron source used in BNCT can come from a reactor, as a condition for conducting BNCT therapy tests, there are five standard parameters that must be met for a neutron source to be used as a source, and the standards come from IAEA. This research is based on simulation using the MCNPX program which aims to optimize IAEA parameters that have been obtained in previous studies by changing the shape of the collimator geometry from cone shape to cylinder with variations diameter from 3, 5 and 10 cm and also the simulation divided into two schemes namely first moderator Al is placed in a position 9.5 cm behind the collimator and the second is the moderator Al is pressed into the base point of the aperture in the collimator. In this work, neutrons originated from Yogyakarta Kartini research reactor have the energy range in the continuous form. The results of the optimization on each scheme of the collimator are compared with the outputs that have been obtained in previous studies where the aperture of the collimator is in the cone shape. The most optimal output obtained from the results is a collimator with a diameter of 5 cm in the second scheme where the results of IAEA parameters that are produced (n/cm2 s) = 2.18E+8, / (Gy-cm2/n) = 6.69E-13, / (Gy-cm2/n) = 2.44E-13,  = 4.03E-01, and J/ = 6.31E-01. These results can still be used for BNCT experiments but need a long irradiation time and when compared to previous studies, the output of the collimator with the diameter of 5 cm is more optimal.Keywords: BNCT, Collimator, IAEA Parameters, MCNPX, Cylindrical shape